Effects of different drying methods on phenolic components and in vitro hypoglycemic activities of pulp extracts from two Chinese bayberry (Myrica rubra Sieb. et Zucc.) cultivars - Zhe Liu; Jiagan Zhang; Shengmin Lu; Weimin Tang; Yibin Zhou; Siew Young Quek (Food Science and Human Wellness)
The effects of two different drying methods, namely hot-air drying and freeze drying, on the phenolic profiles, antioxidant and hypoglycemic activities of pulp extracts from two main Chinese bayberry cultivars (‘Biqi’ or ‘BQ’ and ‘Dongkui’ or ‘DK’) were evaluated. The results showed that ‘BQ’ bayberry provided higher total phenolic (TPC), total flavonoid (TFC) and total anthocyanin (TAC) contents than ‘DK’ bayberry after the same drying method, while its antioxidant and hypoglycemic activities were highly affected by drying method. Freeze-dried samples possessed significantly higher TPC, TFC and TAC, and exhibited more potent antioxidant and hypoglycemic activities than hot-air dried ones (P < 0.05). Freeze-dried ‘DK’ bayberry exhibited similar antioxidant activities and α-amylase inhibitory activity, but higher α-glucosidase inhibition than freeze-dried ‘BQ’ bayberry (P < 0.05). Compared with hot-air dried samples, freeze-dried samples had significantly higher contents of cyanidin-3-O-glucoside, myricitin-3-O-rhamnoside, quercetin-3-O-galactoside, quercetin-3-O-glucoside and quercetin-3-O-rhamnoside, which had been proved to be the main contributors to the in vitro hypoglycemic activities of bayberry pulp extract. All these results demonstrate that freeze drying is more suitable for the preservation of phenolic components in the pulp extract of Chinese bayberry, and the pulp extract of freeze-dried ‘DK’ could be applied as a potential hypoglycemic food additive.